Relationship Between Clinical and Radiographic Findings in Osteoarthritis Knee: A Cross-Sectional Study - Safaa A. Mahran; Amro Y. Elias; Fadwa S. Janbi; Basem S. El-Deek (Journal of King Abdulaziz University: Medical Sciences, 2023)
Several studies have suggested that there is a high discrepancy between clinical and radiographic knee osteoarthritis. The objectives of this study were to examine association between radiographic classification and clinical manifestations of knee osteoarthritis, and to determine if the assessment of individual radiographic features was superior to the general radiographic scale in establishing such a relationship. A total of 125 patients with knee osteoarthritis were enrolled in this study. Radiographic features were assessed with the Kellgren-Lawrence grade scale for general radiographic grading, and a line-drawing atlas for detailed radiographic analysis. The severity of knee pain, stiff ness, and disability were measured using the Western Ontario and McMaster Universities Osteoarthritis Index. Patients’ age and pain duration were found to correlate significantly with knee pain, stiff ness, and disability. No association between general radiographic grading scale and clinical manifestations was found. However in detailed radiographic analysis, osteophyte site at the patellofemoral joint was found to correlate with knee stiff ness. In conclusion, radiographic scores were not found to be closely associated with the clinical features of knee osteoarthritis. The results of knee X-rays should not be used in isolation when a management decision is to be taken for patients with knee osteoarthritis.